The Development of Students’ Learning Autonomy Using Tilawati Method at a Madrasatul Quran in South Kalimantan - Herlina, Silvia; Rahman, M Arinal; Nufus, Zahratun; Handrianto, Ciptro; Masoh, Khoyriyah (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
Mastering the ability to read the Qur'an is an obligation for every Muslim. However, many Quranic learning models are not able to make students proficient in reading the Qur'an and able to practice it in everyday life. This study aims to provide an overview of the impact of learning the Qur'an using the Tilawati method accompanied by a strategy of reward and punishment, evaluation, and collaboration between students on the independence of learning the Qur'an at a madrasatul Quran in South Kalimantan. This research is based on a qualitative method with a case study type. The data of this study were obtained from student observation and validation through interviews with teaching teachers. The results of the study stated that the use of the Tilawati method plus several combination strategies was able to increase students' independence. Students also become more confident and work well with other students during the learning process. Thus, the Tilawati method has great potential to be applied in every Madrasatul Quran.